Walt disnep lion king story book (Grolier Books Lahore, 2020)
Simba, a young lion prince, faces tragedy when his father Mufasa is killed by his uncle Scar. As he grows up, Simba learns about responsibility, courage, and leadership, ultimately reclaiming his rightful place as king of the Pride Lands. It$1 (Bs a tale of redemption and the circle of life.s